Development of Wayground Media Based on Problem-Based Learning To Improve Social Studies Learning Outcomes - Yuni Harti; Imam Sukwatus Suja’i; Ajar Dirgantoro; Rahyu Setiani (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Education aims to develop students’ potential optimally; however, learning outcomes in Indonesia still face challenges, particularly low student engagement due to teacher-centered instruction. In response to the demands of 21st-century learning and technological advancement, interactive digital learning media oriented toward problem solving are needed to improve Social Studies achievement. This study aimed to develop Wayground media based on Problem-Based Learning to enhance the Social Studies learning outcomes of Grade VII students at SMP Negeri 1 Bandung in the first semester of the 2025/2026 academic year. The research employed a Research and Development (R&D) method by adapting and streamlining the Borg and Gall model, including needs analysis, design, product development, expert validation, field testing, revision, and dissemination. The results indicated that the developed media was highly valid based on evaluations by media, material, and language experts. The practicality level exceeded 90.2% across individual, small-group, and large-group trials. The media proved effective, as the mean score increased from 61.27 to 89.71, with an N-Gain of 0.74 (high category) and a statistically significant t-test result (Sig. 0.000 < 0.05). Strengthening the research design and including control groups are recommended for future studies.